PENGEMBANGAN PENDIDIKAN KARAKTER DAN PROFIL PELAJAR PANCASILA BERWAWASAN KEARIFAN LOKAL - Jusmawati Jusmawati; Irnawati Baharuddin; Mahdi Mahdi; Muhammad Fahreza W (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Human life depends heavily on character education, this is because each human being has characteristic differences. Character education is the process of giving guidance to the students to become human in its entirety by having character in the dimensions of thought, heart, taste, sport and karsa. Character education in Indonesia cannot be separated from the values of Pancasila as the guideline of life of the Indonesian nation. Character education based on the profile of students Pancasila can be meant through the education of the workforce, character education, education of values and moral education aimed at giving good or bad decisions, nurturing what is good, and realizing good in everyday life with full heart based on Pancasilla's high values as the philosophy of life of the Indonesian nation. Given the Indonesian territory that consists of many islands and has a wide variety of tribes, cultures and customs that vary so that the cultivation of character values and profiles of Pancasila students with a view of local wisdom this has the aim of improving the quality of maintenance and educational outcomes that lead to the achievement of the formation of character and morality of the personality of students. The values of the character with a view to local wisdom for students of pancasila as the grip of life, the source of morality and ideology of the Indonesian nation are always facing national and global challenges and dynamics. The visual character of local wisdom is closely related to the values of pancasila, because the reflection of Pancasila values is based on the self-esteem of the Indonesian community that is the characteristic of the national personality. This character must be inherited to the young generation for guidelines of life in order to preserve the personality of the nation in accordance with the noble values of the Indonesian nation.